Policy reform and adjustment in the agricultural sectors of developed countries [ - Blandford, David; Hill, Berkeley (Cambridge, Massachusetts : CABI, 2006)
Takes a fresh look at understanding the dynamics of the organic agricultural sector in Europe, Australia, South America, and the US. This book depicts organic agriculture as an engine of growth for the organic sector and examines the important roles plaed by producers, and other parts of the supply chain.
Includes bibliographical references and index
Keywords: Agriculture and state -- European Union countries; Agriculture and state -- North America; Agriculture -- Economic aspects -- European Union countries; Agriculture -- Economic aspects -- North America; Economic stabilization -- European Union countries; Economic stabilization -- North America